If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + (-6) = -11 n + -6 = -11 Reorder the terms: -6 + n = -11 Solving -6 + n = -11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + n = -11 + 6 Combine like terms: -6 + 6 = 0 0 + n = -11 + 6 n = -11 + 6 Combine like terms: -11 + 6 = -5 n = -5 Simplifying n = -5
| 12rs-6s-5s= | | (-4)^2+3*2/-9+4 | | 3a+1=(-3.6)(a+(-1)) | | 4/x=(9/8)*x+1 | | 15=n+(-2) | | 2w=xyz | | 5x+9=6x+10 | | z/2+11=31 | | 5x+4=4x+1 | | -5v=-50 | | 13.25=.06x | | 5/x-4=6/x-3 | | n-(-2)=-3 | | 2=x-(-16) | | -3(2x+3)=18 | | 3(2x-1)+4(6x-7)=29 | | 2.25(4x+(-4))=(-2)+10x+12 | | -8n-4=-2+2+n-6-8n | | 5x=6x^2-1 | | 4/x=9/8x+1 | | 3/5x+1=4 | | 3x+40+x-7=117 | | -x+2x=-14 | | 8-2x=3(1-x) | | 90/0.5 | | 0.5/90 | | y+2x=-19 | | X-(-27)=15 | | 1/7+2x=4x | | -3(7x+9)=69 | | 24=x-(-4) | | x^2-11=24 |